2016
DOI: 10.1002/ijc.30035
|View full text |Cite|
|
Sign up to set email alerts
|

Quadrivalent HPV vaccine effectiveness against high‐grade cervical lesions by age at vaccination: A population‐based study

Abstract: Human papillomavirus (HPV) types 16/18, included in HPV vaccines, contribute to the majority of cervical cancer, and a substantial proportion of cervical intraepithelial neoplasia (CIN) grades 2/3 or worse (CIN2+/CIN3+) including adenocarcinoma in situ or worse. The aim of this study was to quantify the effect of quadrivalent HPV (qHPV) vaccination on incidence of CIN2+ and CIN3+. A nationwide cohort of girls and young women resident in Sweden 2006–2013 and aged 13–29 (n = 1,333,691) was followed for vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 22 publications
(64 reference statements)
7
99
0
2
Order By: Relevance
“…16 In Sweden, a study examining protection from HSIL (CIN2+) found that qHPV VE was 75% for those initiating vaccination before age 17, 46% for those initiating vaccination between 17 and 19 years old, and 22% for women vaccinated at 20-29 years old. 17 In Australia, VE against HSIL was 46% among young women who had completed all three qHPV vaccine doses and 21% for those receiving 2 doses. 15 A second Australian study found that HSIL and LSIL were significantly lower in qHPV vaccinated females with a hazard ratio of 0.72 (0.58-0.91) and 0.76 (0.72-0.80) respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In Sweden, a study examining protection from HSIL (CIN2+) found that qHPV VE was 75% for those initiating vaccination before age 17, 46% for those initiating vaccination between 17 and 19 years old, and 22% for women vaccinated at 20-29 years old. 17 In Australia, VE against HSIL was 46% among young women who had completed all three qHPV vaccine doses and 21% for those receiving 2 doses. 15 A second Australian study found that HSIL and LSIL were significantly lower in qHPV vaccinated females with a hazard ratio of 0.72 (0.58-0.91) and 0.76 (0.72-0.80) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although randomized controlled trials (RCTs) have demonstrated the efficacy of the qHPV vaccine in preventing cervical dysplasia, [11][12][13] vaccine effectiveness (VE) in the general population after the introduction of new vaccines into routine practice can be impacted by ineffective vaccination program design and implementation, poor uptake or adherence to vaccination schedules and contemporaneous changes in risk behaviour. [15][16][17][18][19][20][21] We aimed to estimate the VE of the qHPV vaccine, used in Manitoba's school-based and high-risk public programs, against incident cervical dysplasia and to assess the extent to which VE depended on age at vaccination and number of administered vaccine doses. [15][16][17][18][19][20][21] We aimed to estimate the VE of the qHPV vaccine, used in Manitoba's school-based and high-risk public programs, against incident cervical dysplasia and to assess the extent to which VE depended on age at vaccination and number of administered vaccine doses.…”
Section: Introductionmentioning
confidence: 99%
“…It should though be taken into account that most of the reviewed studies were prone to selection bias as they compared vaccinated with unvaccinated women and mostly reported on cervical abnormalities observed prior to normal screening age. A study from Sweden thus reported a 63% (95% CI 51%–72%) decline in cervical intraepithelial neoplasia (CIN)2+ in women vaccinated when they were ≤16 years based on their screening outcome at the age of 13–22 years 38, 39. This is a larger decline than seen in the FUTURE studies,23 and it could probably be due to the selective character of study data as invitation to screening starts only at the age of 23 years in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 The HPV vaccine is highly efficient and safe, [11][12][13] resulting in a reduction in cervical lesions and condy loma. [14][15][16] However, the vaccine uptake in Strengths and limitations of this study ▪ This is the first interview study about parents' views of including boys in the national schoolbased human papillomavirus vaccination programme in Sweden. ▪ Our study includes parents who had declined as well as parents who had accepted vaccination for their daughter, and the included parents' represent a broad variation of urban and rural areas in different regions.…”
Section: Introductionmentioning
confidence: 99%